Uniformly locally o‐minimal open core. Issue 4 (25th October 2021) - Fujita, Masato
Abstract: This paper discusses sufficient conditions for a definably complete expansion of a densely linearly ordered abelian group to have uniformly locally o‐minimal open cores of the first/second kind and strongly locally o‐minimal open core, respectively.